2010
DOI: 10.1017/s1466252310000149
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation in bacterial pathogens of veterinary importance

Abstract: Bacterial biofilms are structured communities of bacterial cells enclosed in a self-produced polymer matrix that is attached to a surface. Biofilms protect and allow bacteria to survive and thrive in hostile environments. Bacteria within biofilms can withstand host immune responses, and are much less susceptible to antibiotics and disinfectants when compared with their planktonic counterparts. The ability to form biofilms is now considered a universal attribute of micro-organisms. Diseases associated with biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
100
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 185 publications
(340 reference statements)
1
100
0
10
Order By: Relevance
“…In A. pleuropneumoniae, this polymeric matrix has been shown to be involved in the formation of a robust biofilm in a very short period of time (4). Biofilms are sessile communities of microorganisms attached to a biotic or abiotic surface and enclosed in a self-produced extracellular polymer matrix (19,20). These are more frequently associated with chronic diseases due particularly to an increased resistance to both conventional biocides and the host immune system (20)(21)(22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In A. pleuropneumoniae, this polymeric matrix has been shown to be involved in the formation of a robust biofilm in a very short period of time (4). Biofilms are sessile communities of microorganisms attached to a biotic or abiotic surface and enclosed in a self-produced extracellular polymer matrix (19,20). These are more frequently associated with chronic diseases due particularly to an increased resistance to both conventional biocides and the host immune system (20)(21)(22).…”
mentioning
confidence: 99%
“…Biofilms are sessile communities of microorganisms attached to a biotic or abiotic surface and enclosed in a self-produced extracellular polymer matrix (19,20). These are more frequently associated with chronic diseases due particularly to an increased resistance to both conventional biocides and the host immune system (20)(21)(22). In this context, we have shown that A. pleuropneumoniae biofilm cells are 100 to 30,000 times more tolerant to antimicrobials than their planktonic counterparts (23).…”
mentioning
confidence: 99%
“…iofilms are defined as bacterial communities encased in a selfproduced polymeric matrix that is attached to a surface (1). The ability to form a biofilm is virtually a universal trait of bacteria and other microorganisms.…”
mentioning
confidence: 99%
“…The ability to form a biofilm is virtually a universal trait of bacteria and other microorganisms. Growth as a biofilm offers protection against hostile environments, the immune response, and bactericidal concentrations of antibiotics or disinfectants (1). Biofilms have frequently been studied using the 96-microtiter plate model because it is a platform that requires small volumes and is suited for high-throughput screening (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation